1960
DOI: 10.1152/ajplegacy.1960.199.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of radium in dogs

Abstract: Three female adult dogs were injected intravenously with single doses of radium-226 chloride ranging from 20 to 40 µc. Periodic sampling of blood with added heparin and of urine using a bladder catheter were performed for total elapsed times of from 1 week to 21 weeks. Analyses were made of radium in the plasma, the plasma ultrafiltrate and in the urine. Creatinine was determined in plasma and urine. Radium clearance (average = 1.6 ml/min.), creatinine clearance (average = 46 ml/min.), percentage of the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…On the average, 2-4 times more 85Sr than 45Ca was excreted (Table 1). This finding in dogs agrees with earlier reports for rats (Bauer, Carlsson & Tindquist, 1955), rabbits (MacDonald, Noyes & Lorick, 1957), and man (Spencer, Laszlo & Brothers, 1957;Spencer, Li, Samachson & Laszlo, 1960) and a recent report on clearances in dogs (Della Rosa, cited by Hursh, Lovaas, Piccirilli & Putnam, 1960). Sodium. It would appear from the data reported here that sodium flux occurs relatively close to the glomerulus, though perhaps more distally than does calcium flux.…”
Section: Discussionsupporting
confidence: 92%
“…On the average, 2-4 times more 85Sr than 45Ca was excreted (Table 1). This finding in dogs agrees with earlier reports for rats (Bauer, Carlsson & Tindquist, 1955), rabbits (MacDonald, Noyes & Lorick, 1957), and man (Spencer, Laszlo & Brothers, 1957;Spencer, Li, Samachson & Laszlo, 1960) and a recent report on clearances in dogs (Della Rosa, cited by Hursh, Lovaas, Piccirilli & Putnam, 1960). Sodium. It would appear from the data reported here that sodium flux occurs relatively close to the glomerulus, though perhaps more distally than does calcium flux.…”
Section: Discussionsupporting
confidence: 92%
“…Kidney activity cleared rapidly and was not seen in images acquired later than 4 h post-injection. This is not surprising, since studies by Hursh et al demonstrated that 94–97 % of filtered radium was reabsorbed [36]. Furthermore, a study by Lloyd et al [38] of the pharmacokinetics of 226 Ra in beagles revealed low urinary excretion in the range of 6.5 % in the first 10 days and whole-body retention of 72.67 %, indicating that feces was the main route of excretion.…”
Section: Discussionmentioning
confidence: 97%